2019
DOI: 10.1111/1753-0407.12886
|View full text |Cite
|
Sign up to set email alerts
|

Trends in medication utilization, glycemic control and outcomes among type 2 diabetes patients in a tertiary referral center in Singapore from 2007 to 2017

Abstract: Highlights• Medication utilization trends for type 2 diabetes have changed significantly over the years with a shift towards newer agents, and in line with prevailing treatment guidelines. • Metformin is currently the most commonly prescribed glucose-lowering agent, while the use of insulin has increased tremendously in our institution. Use of sulfonylureas decreased, but to a lesser extent than other studies. • Glycemic control has remained largely stable throughout the 11-year study period, but the rate of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
17
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 46 publications
(58 reference statements)
9
17
2
1
Order By: Relevance
“…We found that older adults had better glycaemic control, which is in line with findings from other studies [ 40 42 ]. Possible reasons could be that older patients may have better access to medical care, may be more motivated to receive care, are more adherent with medication use, and are easier to achieve individualized HbA1c target of ≤8% [ 41 , 43 ] The greater gain at glycaemic control rate among the young adults is most likely due to their low initial control rate, leaving more room for improvement as compared with old adults.…”
Section: Discussionsupporting
confidence: 93%
“…We found that older adults had better glycaemic control, which is in line with findings from other studies [ 40 42 ]. Possible reasons could be that older patients may have better access to medical care, may be more motivated to receive care, are more adherent with medication use, and are easier to achieve individualized HbA1c target of ≤8% [ 41 , 43 ] The greater gain at glycaemic control rate among the young adults is most likely due to their low initial control rate, leaving more room for improvement as compared with old adults.…”
Section: Discussionsupporting
confidence: 93%
“…The exception to these changes is the use of metformin, which has remained the most frequently prescribed antihyperglycaemic agent across the years and is still recommended as first‐line treatment in adults following the initial diagnosis of diabetes 39 . Similar medication‐prescribing trends have been reported in international cohorts 10,12,40 . Given the recently reported end‐organ protection afforded by GLP‐1 receptor agonists and SGLT2 inhibitors, it is probable that their future use will further increase in alignment with new guideline recommendations 41 …”
Section: Discussionsupporting
confidence: 54%
“…International treatment guidelines have been updated to reflect individualization of glycemic targets, taking into consideration specific patient factors and risks of atherosclerotic cardiovascular disease and renal complications (5)(6)(7)(8). These changes in management approaches will influence prescribing patterns, which may affect glycemic control, hypoglycemia, and diabetes-related complications (9)(10)(11)(12).…”
mentioning
confidence: 99%